Particle size and metals concentrations of dust from a paint manufacturing plant - Huang, S.L.; Yin, C.Y.; Yap, S.Y. (Elsevier, 2010)
In this study, the particle size distribution and concentration of metallic elements of solvent- and water-based paint dust from bulk dust collected from dust-collecting hoppers were determined. The mean particle size diameter over a 12-week sampling period was determined using a particle size analyzer. The metals composition and concentration of the dust were determined via acid digestion technique followed by concentration analysis using inductively coupled plasma. The volume weighted mean particle diameters were found to be 0.941 +/- 0.016 and 8.185 +/- 0.201 mu m for solvent- and water-based paint dust, respectively. The mean concentrations of metals in solvent-based paint dust were found to be 100 +/- 20.00 mu g/g (arsenic), 1550 +/- 550.00 mu g/g (copper), 15,680 +/- 11,780.00 [mu g/g (lead) and 30,460 +/- 10,580.00 mu g/g (zinc) while the mean concentrations of metals in water-based paint dust were found to be 20.65 +/- 6.11 mu g/g (arsenic), 9.14 +/- 14.65 mu g/g (copper), 57.46 +/- 22.42 mu g/g (lead) and 1660 +/- 1260 mu g/g (zinc). Both paint dust types could be considered as hazardous since almost all of the dust particles were smaller than 10 mu m. Particular emphasis on containment of solvent-based paint dust particles should be given since it was shown that they were very fine in size (<1 mu m) and had high lead and zinc concentrations. (C) 2009 Elsevier B.V. All rights reserved.